Ansel's pharmaceutical dosage forms and drug delivery systems - Allen, Loyd V., Jr.; Ansel, Howard C. (Philadelphia : Wolters Kluwer Health, 2014)
The purpose of this text is to introduce pharamcy students to the principles, praactices, and technologies applied in the preparation of pharmaceutical dosage forms and drug delivery systems.
Introduction to drugs, drug dosage forms, and drug delivery systems -- Drug dosage form and drug delivery system design -- Solid dosage forms and solid modified-release -- Semisolid dosage forms and transdermal systems -- Suppositories, inserts, and sticks -- Liquid dosage forms -- Sterile dosage forms and delivery systems -- Novel and advanced dosage forms, delivery systems, and devices
Includes bibliographical references and index.
Keywords: DOSAGE FORMS; DRUG DELIVERY SYSTEMS